Biology Learning Innovation Using Booklet Media - Andi Muhammad Abrianto; Ijeoma Amaefuna; Agbo Felicia Onyemowo (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to develop booklet-based learning media for the 11th grade Biology subject, as well as to measure the level of validity and effectiveness of the media in improving the learning of Biology for 11th grade students. Methodology: This study uses a development research method with a 4-D approach (define, design, development, disseminate). The subjects of the study were students of class 11 MIA I at Islamic high school Madani Pao-Pao (24 students) and State Islamic High School 1 Makassar (35 students). Data collection techniques were through observation, interviews, and documents. Data were analyzed qualitatively with descriptive presentation. Main Findings: The results of the study showed that the developed booklet-based learning media received validation with an average of 3.5, which means it is very valid. Field trials at Islamic high school Madani Pao-Pao and State Islamic High School 1 Makassar showed that this media was effective, with an average implementation value of 3.6 and 3.1, which were included in the good and very good categories. Positive responses from teachers and students stated that booklets helped increase learning motivation and facilitated understanding of the material. Novelty/Originality of this study: The novelty of this research lies in the development of booklet-based learning media that integrates material summaries with relevant images and quizzes to train students' critical thinking skills. This media is also designed to increase learning motivation through an attractive and practical display, and is adjusted to the curriculum and needs of Islamic high school students.